2022
DOI: 10.1128/mbio.01886-22
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunctional Glymphatic System with Disrupted Aquaporin 4 Expression Pattern on Astrocytes Causes Bacterial Product Accumulation in the CSF during Pneumococcal Meningitis

Abstract: The lack of solute drainage due to a dysfunctional glymphatic system leads to an increase of the neurotoxic bacterial material in the CSF compartments of the brain, ultimately leading to brain-wide neuroinflammation and neuronal damage with consequent impairment of neurological functions. The loss of function of the glymphatic system can therefore be a leading cause of the neurological sequelae developing post-bacterial meningitis.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…Pneumolysin (Ply) is the pore-forming cytotoxin released by S. pneumoniae and can damage the host cells ( 56 , 57 ). Generoso et al, have recently shown that the accumulation of pneumococci and toxic pneumococcal products, such as Ply, in the CSF compartments of the brain leads to neuronal damage with consequent dramatic impairment of neurological functions ( 58 ). Like it was previously described for other bacterial pathogens, pneumococci can exploit the interaction with the host cell cytoskeleton to invade neurons; neuronal cell death occurs due to cytoskeleton disruption ( 59 , 60 ).…”
Section: Neuroinflammation and Role Of Microglia In Bacterial Meningitismentioning
confidence: 99%
“…Pneumolysin (Ply) is the pore-forming cytotoxin released by S. pneumoniae and can damage the host cells ( 56 , 57 ). Generoso et al, have recently shown that the accumulation of pneumococci and toxic pneumococcal products, such as Ply, in the CSF compartments of the brain leads to neuronal damage with consequent dramatic impairment of neurological functions ( 58 ). Like it was previously described for other bacterial pathogens, pneumococci can exploit the interaction with the host cell cytoskeleton to invade neurons; neuronal cell death occurs due to cytoskeleton disruption ( 59 , 60 ).…”
Section: Neuroinflammation and Role Of Microglia In Bacterial Meningitismentioning
confidence: 99%
“…To determine if astrocytes, a key component in the VZ disruption due to the reactive astrogliosis associated with hydrocephalus pathology [ 43 ] and as a structural component of the glymphatic system involved in the parenchymal CSF pathway [ 38 , 44 ], were affected by increased concentrations of DMSO, transwell astrocyte cultures were performed. Astrocyte viability was evaluated in cell cultures ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Perhaps, the protective effect of antimicrobial therapeutics is due to the mitigation of the contribution of infections to the progression of AD pathology. Indeed, experimental studies have revealed significant impairment of the glymphatic system following cerebral infection (e.g., pneumococcal meningitis) [ 151 ], which could exacerbate AD progression at all stages of disease. Moreover, the prolonged activation of immune cells is a central feature of AD and induces a pro-inflammatory cascade that contributes to neuronal loss.…”
Section: Discussionmentioning
confidence: 99%